Pemanfaatan Media Pembelajaran Pak Berbasis Digital Mobile Learning - James Saragih; A.P. P. Undap; Marde C.S Mawikere (Jurnal Ilmiah Wahana Pendidikan, 2021)
This research is to describe and analyze carryng out, the factors supporting and inhibiting, and efforts to overcome obstacles utilization learning media learning-based PAK digital mobile learning. The research approach used is a qualitative descriptive research approach with type of multi site research and a tringulation method, with the research sites located in High School Country 9 Manado in 2020. Date were collected through interview, observation, and documentation techniques. From the finding result carryng out of utilization PAK learning media based on digital mobile learning, it has long been used and has become pilar for education activities in school. PAK theachers use several applications to make it easier, more practical and efficient in terms of providing teaching materials, as well as in work on teacher administration. In learn media utilization there are factors supporting and inhibiting. The supporting factors there are: 1) There is a desire, motivation, integrity from teacher and students, 2) Theacers PAK and students get pulse subsidy assistance, internet quotas from School Operational Assistance fund, 3) Teachers receiver application introduction training. Obstacle factor there are: 1) Internet network connection depend on geograpich location and weather factors, and the operating system on the gadget device used, 2) Internet quota that that is quite large and expensive, 3) Lack of digital literacy skills.To overcome these obstacle, efforts need to be made: 1) Looking for a spot or area internet network connection better, or by replacing the gadget device with a more suitable operating system, 2) Barriers to school internet quota needs provide internet quota subsidies to teachers and students, 3) Throught training (workshops), self taught manner lerning by utilizing educational applications or content as well as using other people as tutors.